The Narrative Of Martyrdom As Postmodern Way Of Doing A Modern Liberation Theology - Albertus Bagus Laksana (STF Driyarkara - Diskursus, 2015)
Abstract: The survival and significance of the Latin American liberation theology movement relies, to some extent, on the power of the narratives of martyrdom. Precisely by relying on these narratives, through the dynamics of the theological category of memory that leads to solidarity, liberation theology situates itself in the tension between modernity and postmodernity. The categories of narrative, memory and solidarity, which are at play in the whole dynamic of martyrdom, constitute a postmodern way of doing a modern liberation theology. Liberation theology will only be able to retain its “liberative” and “theological” element insofar as it continues to be “modern” and “postmodern” at the same time. Against the postmodern disbelief in the possibility of human emancipation, liberation theology continues to labor precisely under principium liberationis grounded in the promise of liberation contained in God’s revelation in the Scriptures. However, against the “modern” conception of emancipation based on reason and governed by the idea of progress, liberation theology envisions liberation as an integral process which takes place in a concrete, particular historical reality and under the eschatological promise of God. Keywords: liberation theology, martyrdom, modern, postmodern, narrative, memory, solidarity. Abstrak: Relevansi dan pertumbuhan teologi pembebasan, sampai tingkat tertentu, juga bergantung pada kekuatan kisah kemartiran. Dengan mendasarkan diri pada kisah (narrative) yang diolah lewat kategori pengingatan (memory) yang mengarah pada solidaritas, teologi pembebasan menempatkan diri dalam tegangan antara modernitas dan posmodernitas. Kategori kisah, pengingatan, dan solidaritas, yang berada dalam jantung narasi kemartiran, mengetengahkan sebuah cara posmodern untuk melakukan teologi pembebasan yang modern. Teologi pembebasan hanya akan berhasil mempertahankan unsur “teologi” dan “pembebasan” sejauh bersifat modern dan posmodern pada saat yang sama. Melawan ketidakpercayaan posmodernitas terhadap kemungkinan proyek pembebasan, teologi pembebasan mempertahankan prinsip pembebasan atas dasar isi pewahyuan Allah dalam Kitab Suci. Akan tetapi, melawan pemahaman modern tentang pembebasan berdasarkan akalbudi dan kemajuan, teologi pembebasan memahami pembebasan sebagai sebuah proses integral yang terjadi dalam waktu dan tempat yang nyata, dalam realitas sejarah yang partikular dan dalam kerangka janji eskatologis Allah. Kata-kata kunci: teologi pembebasan, kemartiran, modern, posmodern, narasi, pengingatan, solidaritas.